Collaborative Governance in Local Policy Dynamics: A Scientometric Analysis of Tripartite Actor Engagement in Makassar City, Indonesia - Erniwati Erniwati; Sitti Murniati Muhtar; Fatma Fatma (Jurnal Pemerintahan dan Politik Lokal, 2026)
This study examines the dynamics of collaborative governance in Makassar City, Indonesia, through a scientometric analysis of academic discourse spanning a decade (2016–2026). Employing the OpenAlex catalog with a Triple-Helix keyword strategy, 14,085 scholarly articles were extracted to investigate perceptual disparities among tripartite governance actors government agencies (OPD), civil society organizations (OMS), and private sector entities using IndoBERT-based sentiment analysis. Findings reveal a competitive academic landscape: positive sentiment (37.0%) marginally surpasses negative sentiment (33.6%), with neutral discourse comprising 29.4%. Cross-actor analysis uncovers significant perceptual dissonance: civil society organizations receive the highest academic criticism (37.1%), whereas government (38.6%) and private sectors (41.9%) dominate positive sentiment. Applying Collaborative Governance Theory, this study argues that the identified actor-specific sentiment disparities reflect structural asymmetries in trust-building mechanisms, institutional design deficits, and facilitative leadership gaps that impede genuine tripartite collaboration